Effect of melatonin on myocardial susceptibility to ischaemia and reperfusion damage in a rat model of high-fat diet-induced obesity - Kaskar, Rafee'ah (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScMedSc)--Stellenbosch University, 2015.